Overview of Waiting Time for Provision of Outpatient Medical Records Based on Minimum Service Standards (SPM) at dr. Mintohardjo Hospital, Jakarta, Indonesia - Azhar Muttaqin; Lily Widjaja; Laela Indawati; Noor Yulia (HM Publisher, 2023)
Timely provision of outpatient medical records results in quality medical record services. The time for providing outpatient records according to minimum service standards is â‰¤ 10 minutes. This study aimed to determine the length of waiting time for outpatient medical records at dr. Mintohardjo Hospital. The method in this research uses a descriptive method with a quantitative approach. The sampling technique used accidental sampling with a sample size based on an estimated proportion of 106 medical records. The research results showed that 14 medical records (13.2%) were on time and 92 medical records (86.8%) were not on time, most of which were not on time, namely > 31-40 minutes, 31 medical records (29.2%). In identifying the causes of delays in providing outpatient medical records, researchers used the 5M factors. Man factor of occurrence of misfile, there are medical records that have not been returned from the polyclinic or inpatient room, and there is a lack of knowledge and education. The money factor has not yet been budgeted for repairing the Roll O Pack. The material factor for printing loan receipts and medical records is not automatic in the SIMRS application, and only 1 printer machine is available out of 7 computers, so the number of printers needs to be increased. Machine factor occurs Roll O Pack damage and interference with software from downtime (the time when a system, application, and service cannot be accessed/does not function) in the SIMRS application. The method factor is that there is no SOP for providing outpatient medical records.